Comparison of the Effectiveness of Providing Blanket Warmers, Warm Parenteral Fluids, and Operating Room Temperature Modification in Preventing Perioperative Hypothermia - I Kadek Purwadadi; Ni Luh Putu Inca Buntari Agustini; I Kadek Nuryanto; Ni Made Manik Elisa Putri (Babali Nursing Research)
Introduction: Perioperative hypothermia can cause various adverse physiological effects if not prevented. Preventing perioperative hypothermia includes using a blanket warmer, warm parenteral fluid, and operating room temperature modification. The research aimed to compare the effectiveness of blanket warmer, warm parenteral fluid, and operating room temperature modification in preventing perioperative hypothermia.